(untitled) (EAAE Annual Conference Proceedings, 2023)
In architecture and urban design education, critique is hard to find anymore: it does seem lost in the call for a renewed disciplinary autonomy, localised territorial interests and the sole artistic and sovereign agency of the maestro.